Implementation of Mathematical Modelling on The Case of Melawi River Sediment Transport through Van Rijn Method - Kurniawan, Muhammad Hafiz; Soeryamassoeka, S.B.; Umar, Umar (Fakultas Teknik Universitas Tanjungpura, 2025)
This study examines sediment transport dynamics in the Melawi River, West Kalimantan, Indonesia, in response to illegal gold mining and uncontrolled sand mining activities. These activities have significantly increased sedimentation rates, negatively impacting the river ecosystem and local communities. This study used the Van Rijn method to analyse bottom sediment transport and suspended sediment transport at 12 monitoring sites along 900 km of the river. This study aims to analyse the rate of sediment transport and suspended sediment transport using the Van Rijn method. To plot the flow velocity and sediment concentration profiles. Derive mathematical equations from these graphs to predict sediment transport in the Melawi River. This comprehensive analysis will provide quantitative data on sediment transport rates, distribution patterns and predictive models of future sediment dynamics. The results will inform effective mitigation strategies, support sustainable river management and the well-being of communities along the Melawi River. The analysis showed that the bottom sediment transport of the Melawi River was 762,404 tonnes/year and the drift sediment transport was 190,245 tonnes/year, resulting in a total sediment transport of 952,649 tonnes/year.